Comparative evaluation of visceral and renal protection methods during thoracoabdominal aortic repair (Experience of Russian Surgery Research Center named after B.V. Petrovsky) - E. Yu. Chepurnyak; Yu. V. Belov; E. R. Charchyan; A. A. Eremenko; L. S. Lokshin; B. A. Аkselrod; O. V. Dymova; K. A. Zinoviev; A. V. Panov (Вестник анестезиологии и реаниматологии)
The objective: to compare the effectiveness of visceral and renal protection methods during thoracoabdominal aortic (TAA) repair: left atrial-femoral bypass (LAFB) and cardiopulmonary bypass (CPB) in conjunction with selective perfusion (SP) of these organs.Subjects: 81 patients who underwent TAA repair were enrolled in retrospective analysis: LAFB was used in 29 patients (Group 1), CPB and SP ‒ in 52 patients (Group 2).Results. In Group 2, there were lower intraoperative blood loss volume (1,500 ml vs 4,200 ml, p < 0.001), significantly lower levels of direct bilirubin, blood creatinine, blood alpha-amylase in postoperative period, significantly shorter duration of hospital stay, ICU stay and duration of mechanical ventilation. Also in this group, there were lower incidence of multiple organ dysfunction (11.5% vs 37.9%, p = 0.005), stroke (0 vs 10.3%, p = 0.043), lower need for requirement (3.8% vs 20.7%, p = 0.022) and mortality (3.8% vs 27.6%, p = 0.003).Conclusion: During TAA repair, CPB in conjunction with selective visceral and renal perfusion is more beneficial for organ protection as compared with LAFB.